O Txondaro e os Guarani: alteridade e intenção - Sian, Matheus Giacomin (2023)
This dissertation presents an ethnography on the meanings of txondaro among the Guarani, highlighting the spectrum of transformation between humans, gods and animals, based on the ways of updating in each specific relationship, in order to reflect on the Guarani ways of knowledge, and of invention of ignorance. Whether in the collective or individual forms of the txondaro, I focus on the relationality of the term, treating the txondaro as a concept of otherness among the Guarani, due to its ability to always indicate the other. Throughout this dissertation, I aim to produce a narrative that aims to answer what brings people together or distances them and I reflect on how the subjects considered txondaro pose questions about consanguinity, potential affinity and antisociality, based on relationships established with birds, bees and the jaguars; cutting the flow of relationality from otherness.